2019
DOI: 10.1002/cphc.201900068
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Coordination of Pb2+ Defects in Hybrid Lead Halide Perovskite Films Using Truxene Derivatives as Lewis Base Interlayers

Abstract: Truxene derivatives, due to their molecular structure and properties, are good candidates for the passivation of defects when deposited onto hybrid lead halide perovskite thin films. Moreover, their semiconductor characteristics can be tailored through the modification of their chemical structure, which allows-upon light irradiation-the interfacial charge transfer between the perovskite film and the truxene molecules. In this work, we analysed the use of the molecules as surface passivation agents and their us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…[25] The presence of such plumbate complexes in the solid-state semiconductor might cause defect states which diminish the optoelectronic properties of the semiconductor. [26][27][28] Therefore, understanding the optoelectronic properties of the precursor solutions may provide deeper insight into the mechanisms that govern the formation and crystallization processes of halide perovskites and unravel the cause for the widely reported high defect tolerance of this material. [29] In this work, we present a study of the optical properties of polyiodide plumbate complexes, [PbI 2 + n ] nÀ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] The presence of such plumbate complexes in the solid-state semiconductor might cause defect states which diminish the optoelectronic properties of the semiconductor. [26][27][28] Therefore, understanding the optoelectronic properties of the precursor solutions may provide deeper insight into the mechanisms that govern the formation and crystallization processes of halide perovskites and unravel the cause for the widely reported high defect tolerance of this material. [29] In this work, we present a study of the optical properties of polyiodide plumbate complexes, [PbI 2 + n ] nÀ .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, understanding the formation mechanism of these building blocks and their properties is of key scientific interest . The presence of such plumbate complexes in the solid‐state semiconductor might cause defect states which diminish the optoelectronic properties of the semiconductor . Therefore, understanding the optoelectronic properties of the precursor solutions may provide deeper insight into the mechanisms that govern the formation and crystallization processes of halide perovskites and unravel the cause for the widely reported high defect tolerance of this material …”
Section: Introductionmentioning
confidence: 99%
“…For instance, the RC24 will have different effects as seen by the increased PL yield, compared to RC25 and RC34. It has been reported that the presence of the Lewis acid–base interactions between the amino group in TPA and the positively charged defects, such as undercoordinated Pb 2+ in the perovskite, cause passivation of surface defects and significantly decrease the nonradiative recombination in perovskite films. This was our initial motivation for the synthesis of the molecules used in this work. Moreover, TPA-based SAMs exhibit good thermal and morphological stability during device fabrication and general operating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The peripheral functionalization via Suzuki reaction allows easy p-electron expansion of the truxene core. 84 Halogenotruxenes react with simple boronic acids [85][86][87][88] and p-expanded derivatives. [89][90][91][92][93][94][95][96] The connection of benzoic acid and benzaldehyde is also possible via this process.…”
Section: Justyna Mech-piskorzmentioning
confidence: 99%